Human engineered cardiac tissue model of hypertrophic cardiomyopathy recapitulates key hallmarks of the disease and the effect of chronic mavacamten treatment - Wang, Kai; Schriver, Brian J.; Aschar-Sobbi, Roozbeh; Yi, Alex Y.; Feric, Nicole T.; Graziano, Michael P. (Frontiers in Bioengineering and Biotechnology, 2023)
The Biowire platform was used to generate 3D engineered cardiac tissues (ECTs) from patientderived induced pluripotent stem cells with a β-myosin mutation (MYH7-R403Q) known to cause hypertrophic cardiomyopathy (HCM) and its isogenic control (WT). After 6 weeks of electrical field stimulation, both WT and R403Q ECTs exhibited mature cardiac phenotypes, including a lack of automaticity and a ventricular-like action potential (AP) with a resting membrane potential < -75mV.Compared to WT, R403Q ECTs demonstrated many HCM-associated pathological changes including increased tissue size and cell volume, shortened sarcomere length and disorganized sarcomere structure. In functional assays, R403Q ECTs showed increased twitch amplitude, slower contractile kinetics, a less pronounced force-frequency relationship and post-rest potentiation, prolonged AP durations, and slowed Ca 2+ transient decay time. Finally, we observed downregulation of calcium handling genes and upregulation of NPPB in R403Q vs. WT ECTs. In an HCM phenotype prevention experiment, ECTs were treated for 5-weeks with 250 nM mavacamten or a vehicle control. We found that chronic mavacamten treatment of R403Q ECTs: (i) shortened relaxation time, (ii) reduced APD90 prolongation, (iii) upregulated ADRB2, ATP2A2, RYR2, and CACNA1C, (iv) decreased B-type natriuretic peptide` (BNP) mRNA and protein expression levels, and (v) increased sarcomere length and reduced sarcomere disarray. Taken together, we demonstrated R403Q ECTs generated in the Biowire platform recapitulated many cardiac hypertrophy phenotypes and that 2 This is a provisional file, not the final typeset article chronic mavacamten treatment prevented much of the pathology. This demonstrates that the Biowire ECTs are well-suited to phenotypic-based drug discovery in a human-relevant disease model.